1998
DOI: 10.5737/1181912x84229234
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and efficiency of nurse-given cancer patient education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Various authors have conducted formal evaluation of alternate methods of closing the informational gap. There is support for more traditional one-on-one counseling [1,19,31], coaching patients to ask questions prior to the consultation process [5], telephone support [7,16], booklets [6], information cards [22], touch screen information systems [11,30], video [8, 14,36], computerized information systems [10, 22,23,24,26,29,32,34], and Internet [4,15,21]. In addition, multi-method approaches may turn out to be most successful [9, 17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have conducted formal evaluation of alternate methods of closing the informational gap. There is support for more traditional one-on-one counseling [1,19,31], coaching patients to ask questions prior to the consultation process [5], telephone support [7,16], booklets [6], information cards [22], touch screen information systems [11,30], video [8, 14,36], computerized information systems [10, 22,23,24,26,29,32,34], and Internet [4,15,21]. In addition, multi-method approaches may turn out to be most successful [9, 17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction significantly increased with the use of a file folder of information booklets and pamphlets among newly-diagnosed cancer patients (p<.0001) (Whelan et al, 1998). However, first-time chemotherapy patients were no more satisfied with use of a teaching book along with a 15-minute, individualized nurse-given patient education session compared with patients receiving the 45-minute standard didactic educational program (Porter, 1998). The one reviewed study which examined patient satisfaction with booklet/pamphlet characteristics found that five cancer booklets differing in content, emphasis, and origin were rated highly by patients with no significant differences found between books (Butow et al, 1998).…”
Section: Mode Of Information Deliverymentioning
confidence: 98%
“…2001), psychological support (McArdle et al. 1996, Maughan & Clarke 2001), community care (Vooght & Richardson 1996, White et al 1996) and disease or treatment site‐specialist nurses (Smith & Waltman 1994, Porter 1995a, 1995b, Porter 1998, White & Wilkes 1999, Campbell et al. 2000, Loftus & McDowell 2000, Ritz et al.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no study has specifically evaluated nurse‐led models of chemotherapy service delivery. A study by Porter (1998) compared the effects of two nurse‐led education programmes on patients’ knowledge during chemotherapy. However, this looked at nurse‐led information provision rather than evaluation of a whole nurse‐led service.…”
Section: Introductionmentioning
confidence: 99%